Pelatihan Sistem Informasi Pengajuan Judul Skripsi (SIPJS) - Fina Ruzika Zaimar; Hasisa Haruna; Wiwin Riski Windarsari; Nur Alim Bahri; Ahmad Ahmad (Universitas Ichsan Sidenreng Rappang, 2025)
Effective and efficient academic services are important indicators in improving the quality of higher education. One of the main challenges faced by study programs is the thesis title submission system which is still done manually, thus triggering various problems such as delays, data irregularities, and difficulties in monitoring by supervisors. Through this community service activity, training on the thesis title submission information system (SIPJS) was conducted for students and lecturers in order to introduce and implement digital technology in the academic administration process. This training uses a participatory approach and direct practice so that participants are able to understand and operate the system optimally. The evaluation results show that SIPJS can increase the efficiency of the title submission process and strengthen the transparency of academic communication between students and lecturers.